Reflections: Improving Medical Students’ Presentation Skills - Tarkowski, Radoslaw (Journal of cancer education, 2017)
Both good communication and presentation skills on the part of an academic teacher are crucial when trying to generate students’ interest in the subject of a lecture. More generally, our task is to share knowledge in the most effective way possible. It is also worth teaching students presentation skills, as today’s students are tomorrow’s teachers. An engaging presentation is a powerful tool. There are some rules for presenting which I consider worthy of being discussed and taught at a medical university.